Medicine and Healing in the Ancient Mediterranean 2014
DOI: 10.2307/j.ctvh1djxz.38
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Analysis of Trauma Patterns in Early Christian Cyprus

Abstract: As author you are licenced to make up to 50 offprints from it, but beyond that you may not publish it on the World Wide Web until three years from publication (September 2017), unless the site is a limited access intranet (password protected). If you have queries about this please contact the editorial department at Oxbow Books

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Malaria, a mosquito‐borne blood disease, is also linked with CO and PH as it can contribute to the development of hemolytic anemias (Angel, 1966; Roberts & Manchester, 2010). Fox et al (2014) suggest that CO and PH could be the result of vitamin B12 deficiency, folic acid deficiency, and congenital hemolytic anemias such as beta‐thalassemia or acquired anemia and malaria. Harper and Fox (2008) also suggested that malaria, among others, was a factor causing the development of hemolytic anemias and skeletal lesions in Cypriot sites, but this theory has not been aDNA tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malaria, a mosquito‐borne blood disease, is also linked with CO and PH as it can contribute to the development of hemolytic anemias (Angel, 1966; Roberts & Manchester, 2010). Fox et al (2014) suggest that CO and PH could be the result of vitamin B12 deficiency, folic acid deficiency, and congenital hemolytic anemias such as beta‐thalassemia or acquired anemia and malaria. Harper and Fox (2008) also suggested that malaria, among others, was a factor causing the development of hemolytic anemias and skeletal lesions in Cypriot sites, but this theory has not been aDNA tested.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of written sources describing living conditions during these periods renders the archeological context and human remains the only sources available to obtain data. Additionally, urban versus rural populations in Cyprus have been only preliminary approached (e.g., Fox, 1997, 2005; Fox et al, 2014; Harper & Fox, 2008; Ioannou, 2013, 2021; Karligkioti et al, 2022), rendering this study one of the first comparative studies in ancient Cyprus. We explore health and stress at urban Nea Paphos, during the Hellenistic–Roman times, compared with people living in the suburbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation